IMPROVING STUDENTS' READING COMPREHENSION ON NARRATIVE TEXT THROUGH QUESTION AND ANSWER RELATIONSHIP (QAR) STRATEGY - Nurhaliza Al-Amiri (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
This study aims to the impact students' reading comprehension through narrative text using the Question Answer Relationship (QAR) strategy. The research was quantitative method using one group pretest-posttest through pre-experimental design. This research was conducted at MTsN 01 Binjai. The population of this study was all students of eighth grade MTsN 01 Binjai in the 2024/2025 academic year as the population. The sample was taken from one class of eighth grade students, namely class VIII-4, consisting of 20 students, with details of 11 females and 9 males. To collect data, this study used pretest and posttest as instruments. The data obtained from the pre-test and post-test were analyzed through hypothesis testing using the T-test. The average pre-test score was 50 and the average post-test score was 85.5. The T-test score result was 14.4. The result is greater than the t-table value at 5% significance, namely t-table (2.093) and a significance value of 1%, t-table (2.861).Thus, the result was in accordance with the criteria of t-test > t-table. Therefore, the alternative hypothesis was accepted. The results of the study showed that there was a significant change in the score of students' reading comprehension skills through narrative texts between the pre-test and post-test. This study shows that students' problems in understanding narrative texts have been solved by using the QAR strategy. In other words, the Question Answer Relationship (QAR) strategy improves students' reading comprehension of narrative texts.